Therapeutic Effect of Chenodeoxycholic Acid in an Experimental Rabbit Model of Osteoarthritis - Yan, Zhao-wei (Mediators Inflamm, 2015)
Osteoarthritis (OA) is a slowly progressive joint disease typically seen in middle-age to elderly people. At present, there is no ideal agent to treat OA. Chenodeoxycholic acid (CDCA) was a principal active constituent from animal bile. However, the therapeutic effect of CDCA on OA severity was largely unknown. The purpose of this study was to evaluate the therapeutic effect of intra-articular injection of CDCA in a rabbit OA model. OA was induced in experimental rabbits by anterior cruciate ligament transection (ACLT) and then rabbits were intra-articularly injected with CDCA (10 mg/kg or 50 mg/kg) once per week for 5 weeks. The results showed that CDCA significantly decreased cartilage degradation on the surface of femoral condyles, reducing the pathological changes of articular cartilage and synovial membrane by macroscopic and histological analysis. CDCA also significantly decreased bone destruction and erosion of joint evaluated by micro-CT. Furthermore, CDCA could markedly reduce the release of matrix metalloproteinase-1 (MMP-1), matrix metalloproteinase-3 (MMP-3), interleukin-1β (IL-1β), and prostaglandin E(2) (PGE(2)) in synovial fluid. These observations highlight CDCA might be a potential therapeutic agent for OA.